Renal recovery after acute kidney injury in a minority population of hospitalized COVID-19 patients: A retrospective cohort study. Issue 11 (18th March 2022) - Sarwal, Amara; Gomez, Edgar; Perez-Gutierrez, Victor; Carlos, Alex; Afzal, Afsheen; Sivakumar, Mangai; Rabah, Sami; Kasubhai, Moiz; Gnanasekaran, Isaiarasi; Menon, Vidya
Abstract : Abstract: This study aimed to characterize survivors of Coronavirus disease 2019 (COVID-19) infection and acute kidney injury (AKI) that recover their renal function or progress to acute kidney disease (AKD) on discharge; and determine factors associated with progression to AKD during hospital stay. One thousand seventy four patients with COVID-19 infection were followed up until discharge/death. The incidence of AKI was 59.7%. Two hundred and sixty-six patients were discharged alive and included in the analysis, 71.8% had renal recovery (RR) while 28.2% were discharged with AKD. The AKD subset has higher rate of chronic kidney disease (CKD) ≥3 (33.4% vs 14.1%, P = .001), congestive heart failure (18.7% vs 5.8%, P = .001), use of non-invasive mechanical ventilation (10.7% vs 3.7%, P = .026) and vasopressors (25.3% vs 12.0%, P = .007). Of 19 patients in the AKI survivor cohort who received renal replacement therapy, 1 had RR while 18 progressed to AKD on discharge. Predictors to progression to AKD were CKD ≥3 (Odds Ratio [OR]: 3.23, 95% confidence interval [CI] 1.59-6.56, P = .001), congestive heart failure (OR: 4.59, 95% CI 1.76-11.78, P = .002), AKI on admission (OR: 2.71, 95% CI, 1.14-6.46, P = .025), and ongoing diarrhea (OR: 3.19, 95% CI, 1.02-9.96, P = .025). This study demonstrates a higher proportion of RR among survivors of COVID-19 infection in our minority predominant cohort. Early identification and appropriate management of patients at-risk to progress to AKD could improve outcomes, reduce long term sequalae of CKD/end stage renal disease, and have a major impact on health outcome and financial strain on healthcare system.